Adv. J Social Sci. 2017
DOI: 10.21467/ajss.1.1.15-29
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Children Ever Born: A Case Study of Somadi Village Development Committee of Palpa District, Nepal

Abstract: A B S T R A C TFertility is one of the three principal components of population dynamics that determine the size, structure, and composition of the population in any country. Children ever born refer to the number of children born alive to the person up to a specified reference date. It includes children who have died since birth. This study aims to identify the socioeconomic and demographic factors influencing Children Ever Born (CEB) to the women of Somadi village development committee (VDC) of Palpa distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
5
4
0
Order By: Relevance
“…The respondents with fewer children ever born (0-2) are middle class and above, while those with low wealth index has more children ever born (>2). This research aligns with that of Upadhyay and Bhandari (2017) in India, stating that family with the lowest income in India has the highest fertility rate, compared to those with lower economic status. It might correlate with other factors, including families with low economy or education status (Upadhyay & Bhandari, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The respondents with fewer children ever born (0-2) are middle class and above, while those with low wealth index has more children ever born (>2). This research aligns with that of Upadhyay and Bhandari (2017) in India, stating that family with the lowest income in India has the highest fertility rate, compared to those with lower economic status. It might correlate with other factors, including families with low economy or education status (Upadhyay & Bhandari, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Viewed from the result of the multivariate test, the age of first marriage is the most dominant factor that determines the fertility rate. The age of first marriage may sustain the chance of reproduction (Arsyad & Nurhayati, 2017;Mulmi, 2018;Upadhyay & Bhandari, 2017). The explanation about the relationship between the age of first marriage and the fertility rate is inverse, meaning that the higher the age of first marriage, the lesser the fertility rate (Larasati et al, 2018;Pratiwi & Herdayati, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study done on Somadi VDC of Palpa district also showed the similar result that 84.3% illiterate women and 83% women whose husbands were illiterate had more than 2 children. 8 Likewise, concurrent result was also found in the study done in Nepal by Aravinda Satyanda,2014. 9 ,N Adhikari,2014.…”
Section: Discussionsupporting
confidence: 57%
“…Similar result was also found in another study done on Palpa district, Nepal where women who had no knowledge of contraceptive had more than 2 children. 8,9 The present study showed that women who had married at the age of (18-24) years were found more proportion to have more than 2 children. Similar results was also found on the study done in Nepal where women of younger age group had more children ever born.…”
Section: Discussionsupporting
confidence: 47%